Variations of the Physical and Mechanical Parameters of Oil Sand under Different Confining Pressure and Temperatures. (29th January 2022) - Yang, Liu; Jiang, Yufei; Gao, Chao
Abstract : Oil sand is an important substitute for conventional oil resources. In this paper, oil sand cores are used to systematically study the mesostructure characteristics of oil sand. Triaxial compression tests under different temperatures and pressures are carried out on oil sand specimens. The research results show that the mineral particles in these oil sands have a loose structure. The particle size distribution of the mineral particles has good continuity. The prepeak deformation characteristics of these oil sands are similar. However, three kinds of postpeak deformation forms are observed: plastic flow, strain softening, and strain hardening. Increasing the temperature can enhance the shear dilatation rate, and the shear dilatation rate decreases nonlinearly with increasing confinement. The compressive strength, residual strength, and elastic modulus increase linearly with increasing confinement. Temperature has little effect on the strength and elastic modulus of oil sand, but it can significantly affect the corresponding Poisson's ratio. The failure modes of oil sand are dominated by shear failure and tensile failure. Under the test condition of 120°C, the thermal stress generated by the high temperature causes the oil sand specimens to produce transverse cracks. These results can provide relevant parameters for the design of oil sand exploration technology.